STRUKTUR KOMUNITAS ZOOPLANKTON DI PERAIRAN SUNGAI KAWASAN PANTAI CEMARA BANYUWANGI - Wijaya, Akbar Sandi; Nugrahani, Magdalena Putri; Putri, Rani Juhana (Nusantara Hasana Berdikari, 2022)
This study aims to determine the community structure of zooplankton in the river waters of the Cemara Banyuwangi Beach area.. Community structure consists of diversity and abundance. The results of diversity obtained 28 species, 8 orders and 11 families, while abundance ranged from 720 - 6391 cells / liter from I - V stations with a total abundance of 17,837 cells / liter. The highest abundance of species is Arcella Hemisphaerica with a total of 3386 cells / l. The life of zooplankton is also influenced by physical and chemical factors of the water. The river Cemara Banyuwangi Beach has a water temperature range of 28 - 31 Â° C, water pH 7,2 â€“ 7,9, salinity 2 - 5 and DO 5,5 - 8 mg / l. The results of the measurement of physical and chemical parameters are in accordance with the conditions of the waters for zooplankton life.